A new dataset of Dutch and Danish party congress speeches. (April 2019) - Schumacher, Gijs; Hansen, Daniel; van der Velden, Mariken A.C.G.; Kunst, Sander
We present a new dataset of speeches given by Danish and Dutch politicians at party congresses between 1946 and 2017. The dataset is a unique collection of materials from different party archives and digital repositories. It offers a unique opportunity to analyse the issues discussed in these speeches, the positions taken and the rhetoric used by party elites over time and between countries. We describe the data and illustrate them with one application: a sentiment analysis that describes differences between parties and over time.